How deteriorating conditions in Myanmar affect migrant domestic workers in Singapore: a transnational analysis of migrant labour regulation - Thazin, Khin (2023)
The COVID-19 pandemic and 2021 military coup in Myanmar have greatly exacerbated the existing economic distress of ordinary people across the country. Yet, what has been the impact of the pandemic and the coup on Myanmar migrant workers abroad? To address this question, we investigate the situation of Myanmar migrant domestic workers (MDWs) in Singapore. We find that pandemic-related economic contraction in Myanmar and heightened insecurity following the country's 2021 military coup have increased outmigration and intensified pressures on Myanmar domestic workers in Singapore to increase remittances and set aside aspirations of shortly returning home. These origin-country conditions, mediated through a transnational system of labour brokerage, have increased Myanmar MDWs’ vulnerability to exploitation and abuse relative to MDWs of other nationalities. This article thus contributes to analysis of the transnational constitution of migrant labour regimes.